Effects of pavement surface temperature on the modification of urban thermal environment - Sarat, Adebayo-Aminu; Eusuf, Muhammad Abu (Institute of Research and Community Outreach Petra Christian University, Indonesia, 2012)
Urban centres continue to experience escalating average summer temperature over the last fifty years. Temperature in the urban core cites have been rising due to rapid growth of urbanization in the latter half of the twentieth century (Akbari et al., 1989). Outdoor experiments were conducted to investigate the effects of different movement of materials on the urban thermal environment. Meteorological conditions such as air temperature, pavement surface temperature, Relative humidity and wind velocity were recorded to determine temperature differences among Asphalt/concrete, interlocking bricks and grass surfaces.